The Influence of Blood Pressure and Chronic Disease to the Elderly’s Quality of Life in Elderly Service Unit of Kartasura Primary Health Care - Triastuti, N Juni; Amalia, Nia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
Quality of life is a person's assumption in terms of culture and values by residence and relates to goals, expectations, concerns, standards during one's life. Elderly who suffer from high blood pressure or chronic disease will affect the quality of life. This is because high blood pressure and chronic illness can adversely affect the function of health, vitality, social, mental and psychological health of the elderly which will ultimately affect their quality of life. This study aims to analyze the effect of blood pressure and chronic disease on quality of life in elderly people in Elderly service unit. This research is an observational analytic research with cross sectional approach. The technique for data sampling of this research is purposive sampling. The data are obtained by measuring the blood pressure and the use of WHOOQOL-BREFF questionnaire. Data analysis used in this research are Chi Square and Logistic Regression analysis. Based on the data analysis, the research finds that blood pressure has significant influence to the quality of life in elderly with p value 0.003. It also finds that chronic disease has a significant effect on quality of life in elderly with p value of 0.000. Based on Logistic Regression analysis finds that the blood pressure and chronic disease factors altogether will significantly affect the quality of life in the elderly with p value of 0.000 and R value of 0.642. The factors of blood pressure and chronic diseases significantly affect the quality of life of the elderly.